The Jakarta Islamic Index (JII) Stock Price In Terms Of Oil, Gold And Exchange Rates - Syafira Indriyani; Nanda Dwi Cahyani; Siti Amaroh (Islamic Economics Journal, 2023)
Stock prices are usually influenced by 2 factors, namely internal factors and external factors. The purpose of this research is to analyze the stock price of the Jakarta Islamic Index (JII) in terms of external factors, namely oil, gold and exchange rates. This study used purposive sampling and quantitative analysis methods for companies that have been consistent in JII for 10 years, and obtained 7 issuers as research specimens. Panel data were processed using multiple linear regression analysis in the SPSS Statistics program version 26. The results of this study indicate that the oil and gold price variables have no effect on JII stock prices, while the exchange rate variable has a positive effect on JII stock prices. Simultaneously the three variables concerned affect the JII stock price by 79.1%, and 20.9% are influenced by factors outside the factors studied. Investors who wish to invest are expected to pay more attention to macroeconomic aspects and to use sharia-based instruments, they can use JII as a reference.